Answer:
Step-by-step explanation:
To prove that -10 is the solution to the given equation, we need to substitute -10 for both x and c and verify if the equation holds true.
Let's start by substituting -10 for x and c in the equation:
1/4(8(-10) - 20) = 6(-10) - (-10 - 25(-10))
Simplifying the equation:
1/4(-80 - 20) = -60 - (-10 + 250)
1/4(-100) = -60 - (-10 + 250)
-25 = -60 - (240)
-25 = -300
The equation is not true when we substitute -10 for x and c. Therefore, -10 is not a solution to the given equation.